Urgensi Pola Perencanaan Karir Aparatur Sipil Negara Dalam Upaya Peningkatan Kinerja - Helen Permata Sari; Dini Oktaviana; Octavia Christina (Sosial Simbiosis : Jurnal Integrasi Ilmu Sosial dan Politik, 2024)
The purpose of this study is to determine how important career planning is for the State Civil Apparatus (ASN) in improving the performance of government organizations. This research highlights the importance of ASN with integrity, professionalism, and free from KKN practices, with reference to the Law of the Republic of Indonesia Number 5 of 2014 concerning ASN. Achieving organizational goals requires effective human resource management, particularly with regard to career planning and development. Data for this study were collected from various sources of related literature using qualitative methodology and literature review strategy. The research findings show that effective career planning can improve ASN competence and job satisfaction, foster employee motivation, and ensure assignments that match skills and interests. Effective career planning also helps retain exceptional workers and produce future leaders capable of leading the organization. Therefore, ASN career planning patterns are beneficial for the personal development of each ASN and also for the organization as a whole.